ANALISIS LOGAM Fe, Cu, Pb, DAN Zn DALAM MINYAK PELUMAS BARU DAN BEKAS MENGGUNAKAN X-RAY FLUORESCENCE - Supriyanto, Agus; -, Alimuddin; -, Bohari (JURNAL ATOMIK, 2018)
A research on the analysis of metals Fe, Cu, Pb, and Zn in lubricating oils new Turbolube 32 and used using X-Ray Fluorescence aims to determine the differences in levels of Fe, Cu, Pb and Zn in the lubricating oil of new and used and know their the effect of duration of use of used lubricating oil to elevated levels of metals Fe, Cu, Pb and Zn in compressors operating system F4K-3. Lubricating oils are used to reduce friction and wear two metal surfaces, the existence and the increase of heavy metals in lubricating oils indicated the occurrence of wear and tear on the engine compressor. From the research, it can be concluded the difference between new and used lubricating oil, lubricating oil does not contain metal new Fe, Pb and Zn but contains Cu amounted to 25.36 mg / L. In Used oil contains metals Fe, Cu and Zn with elevated levels of various metals iron (Fe) 6.243 mg / L, metal Copper (Cu) 41.260 mg / L and zinc (Zn) 32 469 mg / L except metals Lead (Pb) there is no difference between New and Used Lubricating Oil is still 0:00 mg / L or below the Lower Limit of Detection XRF 5.3 mg / L. using Simple Linear Regression correlation coefficient lows of iron (Fe) 0913 and the highest zinc (Zn) 0969 this suggests there is a relationship between duration of use of lubricating oil in the compressor with elevated levels of metals iron (Fe), copper (Cu) and Zinc (Zn). Improved metals in used lubricating oil indicates the wear and tear on the compressor engines except metal Lead (Pb) no elevated levels of metals.